PENGARUH PROFESIONALISME TERHADAP KOMITMEN ORGANISASI DALAM UPAYA MENINGKATKAN KINERJA AUDITOR (STUDI PADA KANTOR PERWAKILAN BPK-RI PROVINSI ACEH ) - Victor D. Siahaan (Jurnal Telaah dan Riset Akuntansi, 2010)
This research is done at BPK branch office  Aceh Province  which aim is to know how big the influence of professionalism and organization commitment toward auditor performance at BPK branch office Aceh Province, and to know if there is or no influence of professionalism to organization commitment at BPK branch office Aceh Province either simultaneously or partially.This research use sample method. Respondens of this research are the auditors at BPK branch office Aceh Province.  The objective of this research is to be able to seek the correlation of professionalism to  organization commitment and auditor performance with 44 auditors samples of populations 78 auditors who is taken at stratifide random sampling. Technics of data analysis the used is path analysis. The analysis indicate that beta scor for the influence of X₁ to X₂ is 0,379, X₁ to Y is 0,485 and X₂ to Y is 0,032.Result of this research indicate that auditor professionalism and organization commitment have significan influence toward auditors performance at BPK branch office Aceh Province by simultaneously. Partially, auditor professionalism have influence to organization commitment and auditors performance at BPK branch office Aceh Province, but do not have influence the organization commitment to auditors performance at BPK branch office Aceh Province by parsially.  Keyword : professionalism, organization commitment, and auditors performance.